Analysis of Japanese Tourists' Experiences in Homestay Services at Popular Marine Tourism Destinations in South Sulawesi Province - Anda Prasetyo Ery; Adi Hendraningrum (Newinera Publisher, 2023)
The aims of the research to analysis of japanese tourists' experiences in homestay services at popular marine tourism destinations. This research used a qualitative research method. The results of the research showed that the service strategy provided must be in accordance with Japanese culture, which always respects time, avoids confrontation, does not ask Japanese tourists personal questions, and does not throw rubbish anywhere. Japanese tourists' sentiments towards Homestay services in popular marine tourism destinations in South Sulawesi Province are based on service, cleanliness, facilities, breakfast and location. Japanese tourist sentiment is positive regarding the services they receive